30 years' follow up of randomised studies of adjuvant CMF in operable breast cancer: cohort study. Issue 7485 (13th January 2005) - Bonadonna, Gianni; Moliterni, Angela; Zambetti, Milvia; Daidone, Maria Grazia; Pilotti, Silvana; Gianni, Luca; Valagussa, Pinuccia
Abstract: Objective To assess the long term effectiveness of adjuvant treatment with cyclophosphamide, methotrexate, and fluorouracil (CMF) in patients with operable breast cancer at risk of relapse, on the basis of three successive randomised trials and one observational study conducted from June 1973 to December 1980. Design Cohort study. Setting Istituto Nazionale Tumori in Milan, Italy. Main outcome measures Relapse free and overall survival, measured by univariate and multivariate analyses. Results After a median follow up of 28.5 years for the initial study, adjuvant CMF was found to reduce the relative risk of relapse significantly (hazard ratio 0.71, 95% confidence interval 0.56 to 0.91, P = 0.005) and death (0.79, 0.63 to 0.98, P = 0.04). Administration of CMF for 12 cycles does not seem superior to a shorter administration of six cycles. In the node negative and oestrogen receptor negative trial, intravenous CMF significantly reduced the relative risk of relapse of disease (0.65, 0.47 to 0.90, P = 0.009) and death (0.65, 0.47 to 0.92, P = 0.01) at a median follow up of 20 years. Conclusions When delivered optimally, CMF benefits patients at risk of relapse of distant disease without evidence of detrimental effects in any of the examined subgroups.